1974
DOI: 10.3758/bf03213953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time and space uncertainty on a vigilance task

Abstract: Two groups, each of 12 Ss, were instructed to detect increments in light level from displays of one or five lights. Signals appeared in regular and in irregular intervals. The display was flashed on simultaneously for 0.8 sec every 3.2 sec. Signal detection was superior with a display of one light than with a display of five lights. For two extreme response criteria, there was a decrement of false alarms and an increment of beta during a run. These changes were not dependent upon time and spatial uncertainty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Consistent with previous findings that spatial uncertainty degrades performance efficiency in vigilance tasks (Adams & Boulter, 1964;Baker, 1958;Bell et al, 1974;Grubb et al, 1995;Helton et al, 2010;Kulp & Alluisi, 1967;Milosevic, 1974;Mouloua & Parasuraman, 1995;Nicely & Miller, 1957), the overall level of signal detections in the present study was significantly lower among observers in the context of spatial uncertainty than in that of certainty.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous findings that spatial uncertainty degrades performance efficiency in vigilance tasks (Adams & Boulter, 1964;Baker, 1958;Bell et al, 1974;Grubb et al, 1995;Helton et al, 2010;Kulp & Alluisi, 1967;Milosevic, 1974;Mouloua & Parasuraman, 1995;Nicely & Miller, 1957), the overall level of signal detections in the present study was significantly lower among observers in the context of spatial uncertainty than in that of certainty.…”
Section: Discussionsupporting
confidence: 92%
“…This is indeed the case. In an illustrative study, Milosevic (1974) asked observers to detect increments in the intensity of flashing lights located in the center and at the four corners of a square. Observers were required only to monitor the center light in the spatial-certainty condition, whereas they were required to monitor all five of the lights in a spatial-uncertainty condition.…”
Section: Introductionmentioning
confidence: 99%
“…If a change in latency had been obtained, this would not directly invalidate the latency model, since in view of the lack of confidence ratings a direct test of the assumption of invariance in lax criterion placements could not be made. In this respect it should be noted that two recent studies have reported time-related increases in stringency for lax criterion placements in vigilance (Milosevic, 1974(Milosevic, , 1975.…”
Section: Discussionmentioning
confidence: 93%
“…Uncertainty during a vigil may also take the form of spatial uncertainty, which can be achieved by varying the probability that signals will appear in different areas of a display/field of view or by using an unpredictable sequence of locations. Spatial uncertainty reduces performance efficiency and causes observers to bias their attention toward those areas of the display where the probability of signal occurrence is the greatest (Adams & Boulter, 1964;Milosevic, 1974;Nicely & Miller, 1957).…”
Section: Spatial Uncertaintymentioning
confidence: 99%